ANALISIS TRADISI PEMAKAMAN TRUNYAN BERDASARKAN PERSPEKTIF SOSIAL BUDAYA DAN HUKUM TERKAIT HAK ASASI MANUSIA PADA MASA COVID-19 - Chandra Putri, Angelina (JURNAL ILMU BUDAYA, 2021)
The COVID-19 pandemic has caused a significant increase in the population mortality rate, with more than 396,000 positive cases and 13,512 deaths as of 27 October 2020 in Indonesia. This requires authorities to issue new stricter funeral protocols. However, in Indonesia, many national cultures that have their funeral practices and traditions. One of the unique and quite famous traditional burial rituals is in the Trunyan area, Bali. The funeral tradition is carried out by placing the body in a special open area and allowing it to be decomposed by nature. This funeral practice is still being carried out today despite the local community's fear of the infamous virus. By using quantitative data and the literature obtained, researchers will analyze the funeral traditions of Trunyan Village from the perspective of culture and law in Indonesia, especially those related to funeral protocols and human rights.